2007
DOI: 10.1093/gerona/62.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Dynamics in Macaques and Humans

Abstract: In humans, telomere length in proliferating tissues shortens with age--a process accelerated with age-related diseases. Thus, telomere length and attrition with age in the nonhuman primate may serve as a useful paradigm for understanding telomere biology in humans. We examined telomere parameters in tissues of young and old Macaca fascicularis and compared them with several tissues from humans. Macaque telomeres were variable in length and exhibited partial synchrony (equivalence) within animals. They were lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 38 publications
8
81
0
Order By: Relevance
“…Furthermore, telomeres in the kidney cortex were significantly longer compared with peripheral blood, suggesting differences in the replicative history of the cells and/or differences in telomere length regulation. Previous studies have shown a correlation between telomere length in different organs in both humans and monkeys (21,22), which was supported by our data on blood and nonmalignant kidney tissue. In addition, we found a surprising correlation between RTL in these compartments and tumor tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, telomeres in the kidney cortex were significantly longer compared with peripheral blood, suggesting differences in the replicative history of the cells and/or differences in telomere length regulation. Previous studies have shown a correlation between telomere length in different organs in both humans and monkeys (21,22), which was supported by our data on blood and nonmalignant kidney tissue. In addition, we found a surprising correlation between RTL in these compartments and tumor tissue.…”
Section: Discussionsupporting
confidence: 91%
“…The tissue distribution of telomerase activity in several species of Macaques (rhesus monkey (Macaca mulatta), Japanese monkey (Macaca fuscata), and crab-eating monkey (Macaca fascicularis)) is similar to humans. Telomerase is repressed in most somatic tissues; low activity is detected in spleen, thymus, and digestive tract, with high activity found in testes (Kakuo et al, 1999;Gardner et al, 2007). Primate telomeres have been reported to be 15-23 kb, which is somewhat longer than in human cells (Kakuo et al, 1999).…”
Section: Primatesmentioning
confidence: 99%
“…However, more recent studies reported telomere lengths from 4 to 16 kb in a few New World primates: spider monkey (Ateles geoffroyi), and squirrel monkey (Saimiri scuireus), and in several Old World primates: rhesus monkey (Macaca mulatta), orangutan (Pongo pygmaeus), and pigmy chimpanzee (Pan paniscus) (Steinert et al, 2002), which are similar to human (Moyzis et al, 1988). The difference may be explained by a longer subtelomeric region in non-human primates (Gardner et al, 2007).…”
Section: Primatesmentioning
confidence: 99%
“…Genetic studies have shown that the telomerase reverse transcriptase (TERT) gene, an enzyme that is fundamental for the accurate de novo synthesis of telomeric ends, is one of the few identified risk loci for pancreatic cancer (8) as well as other tumor types (21). There is evidence pointing to a strong correlation in telomere length across somatic tissues and suggesting that the variability across cell and tissue types is remarkably lower than the interindividual variability of LTL (22)(23)(24), and natural rates of telomere shortening with age appear to follow a pattern of remarkable synchrony across different somatic tissue types (25). These observations identify LTL as a good proxy for overall telomere length and therefore a possibly useful marker for cancer risk.…”
Section: Introductionmentioning
confidence: 99%